Karakteristik Pull - Out Resistance Tulangan Sebagai Perkuatan Pada Tanah Lempung - Said Defri Ariandi; Ferry Fatnanta; Muhardi Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Ground improvement by using reinforcement developed rapidly in recent decades. Since it was first introduced by Vidal (1966), this method is suitable to reduced the deformation of both lateral and vertical deformation. Clay materials used because of its availabilityand lower cost, clay have shown good performance as embankment, and for the reinforcement material using 10 mm steel bar. This laboratory-scale test prepared at two dry side water content, two wet side water content and optimum water content (OMC), while the pullout resistance from longitudinal reinforcement. Pullout resistance reinforcement would be highest when the water content of clay are in optimum condition, adhesi is the dominant force in this pullout resistance test. Keywords: Pullout resistance, water content, reinforcement